教室中的課程政治學：中國大陸教師課程自主權的審視Curricular Politics in Classroom: A Review of Teacher Curriculum Autonomy in Chinese Mainland - 楊明全Mingquan Yan (Higher Education Foundation, 2009)
中國大陸的課程政策一直處於階段性的持續變革之中，但二十世紀末之前的課程政策調整並未賦予教師更大的課程自主權。進入二十一世紀之後，深化素質教育改革、推進教育創新成為中國大陸教育的主流話語，在這一語境之下，教師課程自主權的回歸與重建成為可能。尤其是經過新一輪基礎教育課程改革的洗禮，諸多的課程理念和新的課程價值觀為教師參與課程事務奠定了理論前提和思想基礎，增加了實踐中教師參與發展課程並對國家課程進行調適的空間，由此導致了教室層面教師課程自主權的彰顯和課程創新能力的提高。倡導教師的課程參與、為教師賦權是中國大陸課程領域權力運作的新氣象，也是課程政治學要討論的重要話題。 Even though the curriculum police in Chinese Mainland remains changing in different stages, teachers have not got more curriculum autonomy before 21 century. In this century, it is the mainstream that the education for all-around development reform will be further and the educational innovation will be advanced. In this context, it is possible for the recurrence and reconstruction of teachers' curriculum autonomy. Especially after the recent curriculum reform, many concepts of curriculum and the value-view of new curriculum establish the precondition of theory and the base of idea for teachers' participation in the curriculum, which become the theory base of teacher participation in curriculum change. As a result, teachers' curriculum autonomy will be achieved and teachers will have more and more ability to carry out curriculum innovation and can improve it. It is a new phenomenon in Chinese Mainland that teachers can participate and attain more chances in the process of curriculum change continually, which will be a topic of curricular politics.